ANALISIS TANDA VISUAL CHANNEL IDENTITY MTV (MUSIC TELEVISION) INDONESIA - Aji Windu Viatra (Universitas Trisakti, 2020)
AbstractThe Analysis of MTV (Music Television) Indonesia Channel Identity Visual Symbol. Channel identity can create picture, image, character and identity of a television station. MTV has made the best use of this form of corporate promotion program. Through their channel identity, MTV created images and pictures in accordance with their basic concepts. This research analyzed the MTV (Music Television) channel identity and logo. The analysis procedure carried on the MTV logos including MTV Indonesia, MTV China, MTV Russia, MTV United Kingdom, MTV Japan, and MTV India. This study used a multidisciplinary approach namely the historical, aesthetics, and semiotics approach. The method used in this research was qualitative method, with analytic descriptive analysis. The data was collected through literature study and observation. The data then grouped according to the basic concepts of MTV local culture exploration, and studied by looking at the process of visual idiom design concepts, shapes, characters, colors, and work techniques. The result of this research is interpretation of the visual sign and meaning of the MTV logo as a visual communication media and mass communication which contained certain value and meaning to persuate their audiens. AbstrakAnalisis Tanda Visual Channel Identity MTV (Music Television) Indonesia. Channel identity stasiun televisi dapat membentuk citra, image, karakter dan menjadi identitas sebuah stasiun televisi. MTV telah memanfaatkan sebaik mungkin bentuk program promosi korporat ini. Melalui channel identity, MTV membentuk image dan citra sesuai dengan konsep dasar yang dimiliki. Penelitian ini menganalisis channel identity dan logo stasiun televisi MTV (Music Television). Analisis makna dilakukan pada logo MTV beberapa negara yaitu MTV Indonesia, MTV China, MTV Rusia, MTV United Kingdom, MTV Jepang, dan MTV India. Kajian ini menggunakan pendekatan multidisplin, yakni pendekatan historis, estetika, dan semiotika. Metode penelitian yang digunakan adalah metode kualitatif, dengan analisis deskriptif analitik. Data dikumpulkan melalui studi pustaka dan observasi. Data dikelompokkan sesuai dengan konsep dasar eksplorasi budaya lokal MTV, yang akan dikaji dengan melihat pada proses konsep perancangan idiom visual, bentuk, karakter, warna, dan teknik pengerjaan. Hasil dari penelitian ini adalah interpretasi makna tanda-tanda visual yang digunakan pada logo MTV sebagai media komunikasi visual dan komunikasi massa yang mengandung nilai dan makna tertentu sebagai langkah persuasi kepada pemirsanya. Kata kunci: channel identity, logo, MTV (music television), MTV Indonesia*) J